Microneurosurgery [ aneurysms, arteriovenous malformations - Yasargil, Mahmut Gazi; Thieme Medical Publishers (New York : Thieme Medical Publishers, 2008)
"Named "Man of the Century" by Neurosurgery, the official journal of the Congress of Neurological Surgeons, Dr. Yasargil has been a pioneer in microneurosurgery for decades. The DVD presents the original video series with hours of comprehensive coverage of microneurosurgical techniques. Each video distills Dr. Yasargil's clinical expertise, guiding the clinician step-by-step through the surgical management of aneurysms and arteriovenous malformations."--Publisher Web site.
Presents a series of videos, which provide hours of informative material on the various microneurosurgical techniques. This title takes you through different surgical cases.
Medicine is an ever-changing science undergoing continual development. Research and clinical experience are continually expanding our knowledge, in particular our knowledge of proper treatment and drug therapy. Insofar as this DVD mentions any dosage or application, readers may rest assured that the authors, editors, and pulishers have made every effort to ensure that such references are in accordance with the state of knowledge at the time of production.
DVD-9 ; region 0 ; NTSC ; 4:3
Keywords: Brain -- Anatomy; Brain -- Surgery; Microsurgery; Neurosurgery